Environmental impact assessment of cement factory production on biodiversity: a case study of UNICEM, Calabar Nigeria (2008)
The natural forest at the segment of Southeastern state (Cross River State) is losing its primary status due to various types of human development and industrial activities. This is more envisaged with dry process Kiln method that United Cement Company of Nigeria (UNICEM) intend to use for manufacturing of Cement, which will leave the particulate emission rate of cement as high as 20.8Kg / bbl on the atmosphere. Other environmental pollution problems associated with this activity are bad odour, noise, dust and fumes, aesthetic nuisance, smoke, vibration, effluent and glare. A total of eighty-two tree species among which are some economic species were recorded during the assessment. Diversity Indices of between 0.03 and 1.33 were recorded for the vegetations. Many of the trees are medicinal with the barks and roots used for the treatment of diseases such as malaria, diarrhea, High blood pressure, and skin diseases. Others are cultivated for food, and as ornaments. No disease symptoms were found on the plants within the factory site except that most of the lower plants were dehydrated due to lack of rain. Some of the Rhizophora leaves along the coastline showed some leaf spots, yellowing of leaves and the presence of downy meadews. In conclusion, the industrial activity of UNICEM will in no doubt have impact on habitat vegetation of wildlife species; such species will be compelled to migrate or face mortality. And greater concern must be given to endangered and endemic species such as Pan troglodytes (Chimpanzee), Gorilla gorilla, and Pandrillus leucophaeus that can only be found in this rain forest zone of Cross River National Park.